Controllable Alternating Magnetic Technology Research for Inducing Plants Breeding on Ground - Guo-wen HU; Li-sheng ZHANG; Lin WANG; Yin-jie WANG (Institute of Advanced Engineering and Science, 2013)
Controllable alternating induction magnetic field generation technology which induces plant seeds to breed on floor space has been developed. The incentive ferrite induction coil is used in the device to produce induced magnetic field. The common AC-DC-AC topology was adopted for the variable frequency power supply, realizing the VF. AC-DC-AC AC power inverter circuit adopts SPWM inverter frequency modulation and voltage regulation mode, realizing the effect of sinusoidal variable. In order to improve the conversion efficiency of the system electrical energy to magnetic energy, the RLC series resonant circuit is chosen in the circuit of output magnetic field. The induction magnetic field in the air gap is the work area for seeds experiment. Its adjustable frequency range: 20 200Hz, adjustable field range: 0 500Gs. The experimental study of rice seeds shows that different magnetic environment has a significant impact on the biological characteristics of rice seeds. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2326